A bimetallic selenide heterostructure and preparation and application thereof
Patent Information
- Application Number
- CN202410983532.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-22
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2044-07-22
AI Technical Summary
但是该专利中硒化物合成需要先合成氧化物,然后再硒化,方法繁琐,并且首先需要调控氧化物的形貌和结构
[0061]1、本发明研究了一种新型双金属硒化物异质结构的制备方法,并探讨了其在二次电池中的应用。首先,通过化学还原法制备出具有良好分散性和均匀尺寸的Se纳米棒,并优化其形貌和尺寸。然后,利用Se纳米棒作为模板和硒源,通过溶液法包覆一层双金属有机框架(MOF)。选择适当的金属盐和有机配体,调控金属盐的摩尔比,制备出不同配比的双金属MOF包覆的Se纳米棒。接着,将包覆有双金属MOF的Se纳米棒在氩气保护下进行原位热解,使双金属MOF转化为双金属硒化物纳米颗粒,并在热解过程中形成中空碳管,最终得到双金属硒化物纳米颗粒生长在中空碳管上的异质结构。最后,将该异质结构材料作为锂离子电池的负极材料,进行电化学性能测试,评估其储能性能。通过研究异质结构材料在电化学反应中的电子和离子传输行为,探讨内置电场对反应动力学的影响,验证其在提升二次电池储能性能方面的优势。本发明的研究为高性能双金属硒化物异质结构材料的设计和制备提供了新思路,所制备的材料在二次电池中的应用展现出良好的发展前景和潜力。
Smart Images

Figure CN119079935B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of electrochemical technology, and in particular to a bimetallic selenide heterostructure, its preparation, and its application. Background Technology
[0002] With the rapid development of energy technology, modern society's demand for energy supply is constantly increasing. To reduce dependence on fossil fuels, a shift to sustainable energy is imperative. Rechargeable batteries have attracted much attention due to their high energy density and long cycle life. Over the past three decades, lithium-ion batteries (LIBs) have been widely used in portable electronic products and are considered the most promising power batteries for electric vehicles. The core issue for lithium-ion batteries is further improving their energy density. Currently, graphite is the most common anode material for commercially available lithium-ion batteries; however, the relatively low theoretical capacity of graphite limits the further development of lithium-ion batteries.
[0003] Bimetallic selenides have attracted much attention in the field of electrochemical energy storage due to their unique structure and properties. Compared with single-metal selenides, bimetallic selenides exhibit higher conductivity, better stability, and superior electrochemical performance. However, traditional methods for preparing bimetallic selenides often suffer from problems such as complex procedures, high costs, and difficulty in controlling product morphology, which limit their promotion and application in practical applications.
[0004] In recent years, heterostructured materials have gradually become a research hotspot due to their excellent electrochemical performance, which can effectively promote charge separation and transport through the built-in electric field formed at the interface. By rationally designing and controlling heterostructures, the energy storage performance of materials can be significantly improved. However, how to achieve the efficient synthesis of bimetallic selenides and construct heterostructures with excellent electrochemical performance remains an urgent problem to be solved.
[0005] Chinese patent CN201910976646.6 discloses a method for preparing a sodium-ion battery anode material using bimetallic selenides. This method synthesizes a MoSe2@CoSe2@C heterostructure through a simple process to enhance the electrochemical performance of sodium-ion batteries. The method first synthesizes MoO3 nanorods, then grows a layer of Co-MOF nanosheets on the surface of the MoO3 nanorods. After high-temperature selenization and calcination, a core-shell structure with a uniform heterostructure interface is obtained, which can improve ion diffusion kinetics and increase electronic conductivity, thereby improving the battery's electrochemical performance. Compared with pure MoSe2, SIBs using the MoSe2@CoSe2@C heterostructure as the anode exhibit significantly improved specific capacity, excellent cycle stability, and rate performance. However, the selenide synthesis in this patent requires the prior synthesis of oxides followed by selenization, a cumbersome method that first requires controlling the morphology and structure of the oxides. Summary of the Invention
[0006] The purpose of this invention is to address the problems existing in the prior art by providing a bimetallic selenide heterostructure, its preparation, and its application. This invention utilizes selenium nanorods (Se nanorods) as templates and selenium sources, coating them with a bimetallic organic framework (bimetallic MOF), and synthesizes a heterostructure of bimetallic selenide nanoparticles grown on hollow carbon nanotubes via in-situ pyrolysis. This method cleverly utilizes the role of Se nanorods as templates and selenium sources for one-dimensional structures, combined with the tunability of bimetallic MOFs, allowing for the formation of various bimetallic selenide heterostructures with different metal combinations, ultimately yielding diverse bimetallic selenide heterostructures. This heterostructure possesses an internal electric field, which accelerates electron and ion transport, thereby speeding up reaction kinetics and significantly improving the energy storage performance of secondary batteries. Applying this bimetallic selenide heterostructure to electrode materials in secondary batteries demonstrates excellent energy storage performance with high capacity, high rate capability, and long cycle life.
[0007] The objective of this invention can be achieved through the following technical solutions:
[0008] A method for preparing a bimetallic selenide heterostructure, comprising the following specific steps:
[0009] S1. Synthesis of selenium nanorods (Se nanorods):
[0010] Selenium nanorods were obtained by stirring and mixing sodium carboxymethyl cellulose (CMC-Na) solution, NaOH solution, H2SeO3 solution and NaBH4 solution.
[0011] S2, Bimetallic Organic Framework (Bimetallic MOF) Coated Selenium Nanorods:
[0012] Selenium nanorods obtained in step S1, polyvinylpyrrolidone (PVP), two metal salts and 2-methylimidazole were added sequentially to a methanol solution and stirred to obtain selenium nanorods coated with a bimetallic organic framework.
[0013] S3. Synthesis of bimetallic selenide heterostructures:
[0014] The selenium nanorods coated with a bimetallic organic framework obtained in step S2 were subjected to high-temperature annealing under inert gas protection to obtain a bimetallic selenide heterostructure.
[0015] Further, in step S1, the volume ratio of the sodium carboxymethyl cellulose (CMC-Na) solution, NaOH solution, H2SeO3 solution and NaBH4 solution is (1-10):1:(1-5):(0.1-0.5).
[0016] Further, in step S1, the concentration of the sodium carboxymethyl cellulose solution is 0.1-2.0 g / L.
[0017] Further, in step S1, the concentration of the NaOH solution is 0.01-2.0M.
[0018] Further, in step S1, the concentration of the H2SeO3 solution is 0.01-2.0M.
[0019] Further, in step S1, the concentration of the NaBH4 solution is 0.01-2.0M.
[0020] Further, in step S1, the molar ratio of the NaOH solution to the H2SeO3 solution is 1:1 to 1:5.
[0021] Further, in step S1, the steps for synthesizing selenium nanorods are as follows:
[0022] Sodium carboxymethyl cellulose was dissolved in water, and then NaOH solution and H2SeO3 solution were added under stirring. After stirring until the solution became transparent, NaBH4 solution was added dropwise. After stirring at room temperature for a period of time, a brown suspension was obtained. The solid product was collected by centrifugation, washed three times with deionized water and ethanol, and then vacuum dried to obtain selenium nanorods.
[0023] Furthermore, the stirring time is 1-6 hours.
[0024] Furthermore, the vacuum drying temperature is 40-90℃, and the drying time is 1-24 hours.
[0025] Further, in step S2, the methanol solution: selenium nanorods: polyvinylpyrrolidone: two metal salts: 2-methylimidazole = 180mL: (0.2g~0.5g): 1g: (0.5g~5g): 0.5g.
[0026] Furthermore, in step S2, the polyvinylpyrrolidone is PVP-K30.
[0027] The dosage of PVP(K-30) is 1g.
[0028] Furthermore, in step S2, the two metal salts are selected from any of the following combinations:
[0029] (1)Zn(NO3)2·6H2O and Co(NO3)2·6H2O,
[0030] (2) Zn(NO3)2·6H2O and molybdenum acetate,
[0031] (3) Zn(NO3)2·6H2O and molybdenum nitrate.
[0032] Furthermore, in step S2, the molar ratio of the metal elements in the two metal salts is 1:2 to 1:20.
[0033] Furthermore, in step S2, the mass ratio of 2-methylimidazole to metal salt is 1:1 to 1:10.
[0034] Further, in step S2, the process of coating selenium nanorods with a bimetallic organic framework is as follows:
[0035] The selenium nanorods obtained in step S1 were dispersed in methanol, a certain amount of polyvinylpyrrolidone was added, and after stirring, methanol solutions of two metal salts were added, followed by methanol solution of 2-methylimidazole. After stirring for a period of time, the bimetallic selenide precursor was collected by centrifugation, washed several times with methanol, and then vacuum dried to obtain selenium nanorods coated with a bimetallic organic framework.
[0036] Furthermore, the concentration of the methanol solution of 2-methylimidazole is 0.1-2.0 g / L.
[0037] Furthermore, the stirring time is 30 minutes to 6 hours.
[0038] Furthermore, the vacuum drying temperature is 40-90℃, and the drying time is 1-24 hours.
[0039] Furthermore, in step S3, the heat preservation temperature is 600-900℃, and the heat preservation time is 1-6 hours.
[0040] Furthermore, in step S3, the inert gas is argon.
[0041] Further, in step S3, the step of synthesizing the bimetallic selenide heterostructure is as follows:
[0042] The selenium nanorods coated with a bimetallic organic framework obtained in step S2 were heated from room temperature to high temperature at a certain heating rate under inert gas protection, and held at high temperature for a certain time. After natural cooling, a bimetallic selenide heterostructure was obtained.
[0043] Furthermore, the heating rate is 1-10℃ / min.
[0044] The present invention also provides a bimetallic selenide heterostructure, wherein the bimetallic selenide heterostructure obtained by the above preparation method is composed of bimetallic selenide nanoparticles and hollow carbon nanotubes, wherein the bimetallic selenide nanoparticles are attached to the hollow carbon nanotubes.
[0045] Furthermore, the diameter of the bimetallic selenide nanoparticles is 5-20 nm.
[0046] Furthermore, the bimetallic selenide nanoparticles are randomly distributed and embedded in the wall of the hollow carbon nanotube.
[0047] Furthermore, the present invention also provides an application of a bimetallic selenide heterostructure, which is used to prepare electrode materials for secondary batteries.
[0048] Furthermore, the secondary battery is a lithium-ion battery.
[0049] The bimetallic selenide heterostructure, as an anode material for lithium-ion batteries, exhibits excellent energy storage performance with high capacity, high rate capability, and long cycle life.
[0050] Furthermore, the preparation method of the negative electrode material of the lithium-ion battery is as follows:
[0051] S1. Mix the bimetallic selenide heterostructure, acetylene black and polyvinylidene fluoride (PVDF), add N-methylpyrrolidone (NMP) as solvent, and grind into a uniform black slurry;
[0052] S2. The black paste obtained in step S1 is evenly coated onto the copper foil.
[0053] S3. The electrode sheet coated in step S2 is dried in a vacuum drying oven to obtain a lithium-ion battery negative electrode sheet, which is then assembled and its performance tested.
[0054] Furthermore, in step S1, the mass ratio of the bimetallic selenide heterostructure, acetylene black, and polyvinylidene fluoride is 6:1:1 to 10:1:1, preferably 8:1:1.
[0055] Furthermore, in step S1, the mass ratio of the bimetallic selenide heterostructure to N-methylpyrrolidone is 1:5.
[0056] Furthermore, in step S2, the coating thickness is 50–200 μm, preferably 100 μm.
[0057] Furthermore, in step S3, the vacuum drying temperature is 60–100°C, and the drying time is 6–24 hours.
[0058] The technical principle of this invention is as follows:
[0059] Based on the confinement effect of graphite carbon cages, by injecting a chalcogenide precursor solution into the carbon cage, the chalcogenides grow uniformly within the confined space of the carbon cage, forming chalcogenides with a short-range ordered structure. This structure not only improves the structural stability and conductivity of the material, but also effectively alleviates the volume expansion problem of lithium-ion battery anode materials during charge and discharge processes, and accelerates reaction kinetics, thereby improving the overall performance of the battery.
[0060] Compared with the prior art, the present invention has the following beneficial effects:
[0061] 1. This invention investigates a novel method for preparing bimetallic selenide heterostructures and explores their application in secondary batteries. First, Se nanorods with good dispersibility and uniform size are prepared via chemical reduction, and their morphology and size are optimized. Then, using the Se nanorods as templates and selenium sources, a bimetallic organic framework (MOF) is coated onto the Se nanorods via a solution method. By selecting appropriate metal salts and organic ligands and controlling the molar ratio of the metal salts, Se nanorods coated with bimetallic MOFs in different ratios are prepared. Next, the Se nanorods coated with bimetallic MOFs are subjected to in-situ pyrolysis under argon protection, transforming the bimetallic MOFs into bimetallic selenide nanoparticles. Hollow carbon nanotubes are formed during the pyrolysis process, ultimately yielding a heterostructure of bimetallic selenide nanoparticles grown on hollow carbon nanotubes. Finally, this heterostructure material is used as the anode material in a lithium-ion battery, and its electrochemical performance is tested to evaluate its energy storage performance. By studying the electron and ion transport behavior of heterostructured materials in electrochemical reactions, this invention explores the influence of the built-in electric field on reaction kinetics and verifies its advantages in improving the energy storage performance of secondary batteries. This research provides new ideas for the design and preparation of high-performance bimetallic selenide heterostructured materials, and the prepared materials show promising development prospects and potential for application in secondary batteries.
[0062] 2. Efficient preparation: This invention uses selenium nanorods as templates and selenium sources, and coats them with bimetallic MOFs. The heterostructure of bimetallic selenide nanoparticles grown on hollow carbon nanotubes is synthesized by in-situ pyrolysis, which simplifies the synthesis steps and improves the preparation efficiency.
[0063] 3. Flexible combination: By selecting different metal sources, the composition of bimetallic selenides can be easily adjusted, thereby preparing heterostructure materials with different properties and broadening the application range of the materials.
[0064] 4. Excellent performance: The bimetallic selenide heterostructure has a built-in electric field, which can accelerate the transport of electrons and ions, thereby accelerating reaction kinetics and significantly improving the energy storage performance of secondary batteries, exhibiting the advantages of high capacity, high rate capability and long cycle life.
[0065] 5. Stabilizing the structure: Using selenium nanorods as templates for one-dimensional structures helps maintain the structural stability of materials during electrochemical cycling, reduces capacity decay, and improves the cycle stability and durability of batteries.
[0066] 6. Environmentally friendly: The synthesis process in this invention is relatively mild, and the reaction conditions are easy to control, which reduces the impact on the environment. At the same time, it improves the controllability and consistency of the materials and has good prospects for industrial application.
[0067] 7. Compared with existing technologies, the bimetallic selenide designed in this invention involves first synthesizing Se nanorods, then coating the Se nanorods with a bimetallic MOF, followed by pyrolysis to obtain a hollow nanostructured bimetallic selenide. Conventional selenide synthesis requires first synthesizing oxides and then selenizing them, a cumbersome method that necessitates controlling the morphology and structure of the oxides. In this invention, the Se nanorods serve as both a template for the one-dimensional structure and a Se source. Furthermore, the choice and ratio of the bimetallic metals are flexible when coating the bimetallic MOF, and the method can be flexibly controlled to synthesize any two metal selenides, such as CoSe-ZnSe or MoSe-ZnSe, while maintaining the hollow nanotube structure. The hollow bimetallic selenide prepared by this invention effectively mitigates volume expansion during charging and discharging, exhibiting better structural stability than solid nanowires.
[0068] In summary, this invention has significant advantages in improving the lithium storage performance, conductivity, and process simplicity of lithium-ion battery anode materials, and has broad application prospects and market value. Attached Figure Description
[0069] Figure 1 This is a SEM image of the Se nanorods prepared in Example 1.
[0070] Figure 2 This is a SEM image of the Se nanorods coated with bimetallic Zn-Co MOF prepared in Example 1.
[0071] Figure 3 This is a TEM image of the ZnSe / CoSe heterostructure obtained in Example 1.
[0072] Figure 4 The image shows the XRD pattern of the ZnSe / CoSe heterostructure obtained in Example 1.
[0073] Figure 5 This is a high-resolution TEM image of the ZnSe / CoSe heterostructure obtained in Example 1.
[0074] Figure 6 The graph shows the cycling performance of the ZnSe / CoSe heterostructure prepared in Example 1. Detailed Implementation
[0075] The present invention will now be described in detail with reference to the accompanying drawings and specific embodiments. These embodiments are based on the technical solution of the present invention and provide detailed implementation methods and specific operating procedures. However, the scope of protection of the present invention is not limited to the following embodiments.
[0076] The following detailed description of some embodiments of the present invention is provided in conjunction with the accompanying drawings. Unless otherwise specified, the following embodiments and features can be combined with each other.
[0077] Example 1
[0078] This embodiment provides a method for preparing a bimetallic selenide heterostructure, the specific steps of which are as follows:
[0079] (1) Synthesis of selenium nanorods:
[0080] 1 g of sodium carboxymethyl cellulose (CMC-Na) was dissolved in 10 mL of water, and then 10 mL of NaOH solution (1.0 M) and 10 mL of H₂SeO₃ solution (1.0 M) were added with stirring. When the solution became clear, NaBH₄ solution (1.0 mL, 1.0 M) was added dropwise. After stirring at room temperature for 3 hours, the mixture became a brown suspension. The solid product was collected by centrifugation, washed three times with deionized water and ethanol, and then vacuum dried at 60 °C for 12 hours to obtain Se nanorods. (See attached image) Figure 1 As shown, the SEM images of Se nanorods demonstrate that this method successfully prepared one-dimensional nanorod structures.
[0081] (2) Synthesis of bimetallic selenide heterostructures:
[0082] 0.3 g of Se nanorods were dispersed in 90 mL of methanol, and 1 g of PVP (K-30) was added. The mixture was stirred continuously, followed by the addition of 0.5 g of Zn(NO3)2·6H2O and Co(NO3)2·6H2O, maintaining a metal element molar ratio of 1:16 for both salts. The mixture was stirred for 2 hours. Subsequently, 0.5 g of 2-methylimidazole was weighed and dissolved in 90 mL of methanol. The solution was slowly mixed and stirred for 30 minutes. The precursor (Se nanorods@Zn-Co MOF) was collected by centrifugation, washed 2-3 times with methanol, and then vacuum dried at 60 °C for 12 hours.
[0083] (3) Synthesis of bimetallic selenide heterostructures:
[0084] The dried sample was heated from room temperature to 700℃ at a heating rate of 5℃ / min under argon protection, held at that temperature for 3 hours, and then allowed to cool naturally to obtain a bimetallic selenide heterostructure.
[0085] As attached Figure 2 As shown in the SEM image of the Se nanorod-coated bimetallic Zn-Co MOF, the MOF coating on the outside can be observed.
[0086] As attached Figure 3 As shown, the TEM image of the ZnSe / CoSe heterostructure reveals a hollow tubular structure.
[0087] As attached Figure 4 As shown, the XRD pattern of the ZnSe / CoSe heterostructure indicates the presence of two phases, ZnSe and CoSe.
[0088] As attached Figure 5 The high-resolution TEM image of the ZnSe / CoSe heterostructure shown in the image demonstrates that this method successfully grew two heterostructures together and that a heterojunction exists.
[0089] Furthermore, this embodiment also provides an application of a bimetallic selenide heterostructure, which is used to prepare a negative electrode material for lithium-ion batteries.
[0090] In this embodiment, the preparation method of the negative electrode material of the lithium-ion battery is as follows:
[0091] The bimetallic selenide heterostructure prepared above was mixed with acetylene black and polyvinylidene fluoride (PVDF) at a mass ratio of 8:1:1, and N-methylpyrrolidone (NMP) was added as a solvent. The mixture was then ground into a uniform black slurry. The slurry was uniformly coated onto a copper foil to a thickness of 100 μm. The coated electrode sheet was dried in a vacuum drying oven at 80 °C for 12 hours to obtain a lithium-ion battery negative electrode sheet.
[0092] Battery assembly and performance testing:
[0093] The prepared negative electrode sheet was assembled with a lithium metal sheet into a coin cell using a standard electrolyte. The charge-discharge performance of the coin cell was tested, as shown in the attached figure. Figure 6 As shown in the figure, the cycling performance of the ZnSe / CoSe heterostructure illustrates that after 100 cycles at a current density of 0.2 A / g, the specific capacity remains at 1419 mAh g. -1 Therefore, the bimetallic selenide heterostructure prepared by this method has excellent energy storage performance as a lithium-ion anode material, including high capacity, high rate capability, and long cycle stability.
[0094] Example 2
[0095] This embodiment provides a method for preparing a bimetallic selenide heterostructure, the specific steps of which are as follows:
[0096] (1) Synthesis of selenium nanorods:
[0097] 1 g of sodium carboxymethyl cellulose (CMC-Na) was dissolved in 30 mL of water, and then 10 mL of NaOH solution (1.0 M) and 10 mL of H₂SeO₃ solution (1.0 M) were added with stirring. When the solution became clear, NaBH₄ solution (1.0 mL, 1.0 M) was added dropwise. After stirring at room temperature for 3 hours, the mixture became a brown suspension. The solid product was collected by centrifugation, washed three times with deionized water and ethanol, and then vacuum dried at 60 °C for 12 hours to obtain Se nanorods.
[0098] (2) Synthesis of bimetallic selenide heterostructures:
[0099] 0.5 g of the obtained Se nanorods were dispersed in 90 mL of methanol containing 1 g of PVP (K-30) and stirred continuously. Then, 0.5 g of Zn(NO3)2·6H2O and Co(NO3)2·6H2O were added, controlling the molar ratio of the two metal salts to be 1:4, and stirred for 2 hours. Subsequently, 0.5 g of 2-methylimidazole was weighed and dissolved in 90 mL of methanol. The above solution was slowly mixed and stirred for 30 minutes. The precursor (Se nanorods@Zn-Co MOF) was collected by centrifugation, washed 2-3 times with methanol, and then vacuum dried at 60 °C for 12 hours.
[0100] (3) Synthesis of bimetallic selenide heterostructures:
[0101] The dried sample was heated from room temperature to 700℃ at a heating rate of 5℃ / min under argon protection, held at that temperature for 3 hours, and then allowed to cool naturally to obtain a bimetallic selenide heterostructure.
[0102] Furthermore, this embodiment also provides an application of a bimetallic selenide heterostructure, which is used to prepare a negative electrode material for lithium-ion batteries.
[0103] In this embodiment, the preparation method of the negative electrode material of the lithium-ion battery is as follows:
[0104] The bimetallic selenide heterostructure prepared above was mixed with acetylene black and polyvinylidene fluoride (PVDF) at a mass ratio of 8:1:1, and N-methylpyrrolidone (NMP) was added as a solvent. The mixture was then ground into a uniform black slurry. The slurry was uniformly coated onto a copper foil to a thickness of 200 μm. The coated electrode sheet was dried in a vacuum drying oven at 80 °C for 12 hours to obtain a lithium-ion battery negative electrode sheet.
[0105] Battery assembly and performance testing:
[0106] The prepared negative electrode sheet was assembled with a lithium metal sheet to form a coin cell, and a standard electrolyte was used. The charge-discharge performance of the coin cell was tested, and the results showed that after 100 cycles at a current density of 0.2 A / g, the capacity remained at 1419 mAh / g, with a capacity retention of 98.2%. Therefore, this bimetallic selenide heterostructure exhibits excellent energy storage performance as a lithium-ion negative electrode material, including high capacity, high rate capability, and long cycle stability.
[0107] Example 3
[0108] This embodiment provides a method for preparing a bimetallic selenide heterostructure, the specific steps of which are as follows:
[0109] (1) Synthesis of selenium nanorods:
[0110] 2 g of sodium carboxymethyl cellulose (CMC-Na) was dissolved in 80 mL of water, and then 10 mL of NaOH solution (1.0 M) and 10 mL of H₂SeO₃ solution (1.0 M) were added with stirring. When the solution became clear, NaBH₄ solution (1.0 mL, 1.0 M) was added dropwise. After stirring at room temperature for 3 hours, the mixture became a brown suspension. The solid product was collected by centrifugation, washed three times with deionized water and ethanol, and then vacuum dried at 60 °C for 12 hours to obtain Se nanorods.
[0111] (2) Synthesis of bimetallic selenide heterostructures:
[0112] 0.2 g of the obtained Se nanorods were dispersed in 90 mL of methanol containing 1 g of PVP (K-30) and stirred continuously. Then, 0.5 g of Zn(NO3)2·6H2O and Co(NO3)2·6H2O were added, controlling the molar ratio of the two metal salts to be 1:8, and stirred for 2 hours. Subsequently, 0.5 g of 2-methylimidazole was weighed and dissolved in 90 mL of methanol. The above solution was slowly mixed and stirred for 30 minutes. The precursor (Se nanorods@Zn-Co MOF) was collected by centrifugation, washed 2-3 times with methanol, and then vacuum dried at 60 °C for 12 hours.
[0113] (3) Synthesis of bimetallic selenide heterostructures:
[0114] The dried sample was heated from room temperature to 700℃ at a heating rate of 5℃ / min under argon protection, held at that temperature for 3 hours, and then allowed to cool naturally to obtain a bimetallic selenide heterostructure.
[0115] Furthermore, this embodiment also provides an application of a bimetallic selenide heterostructure, which is used to prepare a negative electrode material for lithium-ion batteries.
[0116] In this embodiment, the preparation method of the negative electrode material of the lithium-ion battery is as follows:
[0117] The bimetallic selenide heterostructure prepared above was mixed with acetylene black and polyvinylidene fluoride (PVDF) at a mass ratio of 8:1:1, and N-methylpyrrolidone (NMP) was added as a solvent. The mixture was then ground into a uniform black slurry. The slurry was uniformly coated onto a copper foil to a thickness of 150 μm. The coated electrode sheet was dried in a vacuum drying oven at 80 °C for 12 hours to obtain a lithium-ion battery negative electrode sheet.
[0118] Battery assembly and performance testing:
[0119] The prepared negative electrode sheet was assembled with a lithium metal sheet into a coin cell using a standard electrolyte. The charge-discharge performance of the coin cell was tested, and the bimetallic selenide heterostructure, as a lithium-ion negative electrode material, exhibited excellent energy storage performance, including high capacity, high rate capability, and long cycle stability.
[0120] The above description of the embodiments is provided to enable those skilled in the art to understand and use the invention. It will be apparent to those skilled in the art that various modifications can be made to these embodiments, and the general principles described herein can be applied to other embodiments without inventive effort. Therefore, the present invention is not limited to the above embodiments, and any improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the invention should be within the protection scope of the present invention.
Claims
1. A method for preparing a bimetallic selenide heterostructure, characterized in that, The specific steps are as follows: S1. Synthetic selenium nanorods: Selenium nanorods were obtained by stirring and mixing sodium carboxymethyl cellulose solution, NaOH solution, H2SeO3 solution and NaBH4 solution. S2, Bimetallic Organic Framework-Coated Selenium Nanorods: Selenium nanorods obtained in step S1, polyvinylpyrrolidone, two metal salts and 2-methylimidazole were added sequentially to a methanol solution and stirred to obtain selenium nanorods coated with a bimetallic organic framework. S3, Synthesis of bimetallic selenide heterostructures: The selenium nanorods coated with a bimetallic organic framework obtained in step S2 were subjected to high temperature preservation under inert gas protection to obtain a bimetallic selenide heterostructure. In step S2, the methanol solution: selenium nanorods: polyvinylpyrrolidone: two metal salts: 2-methylimidazole = 180mL: (0.2g~0.5g): 1g: (0.5g~5g): 0.5g; The two metal salts are selected from any of the following combinations: (1) Zn(NO3)2·6H2O and Co(NO3)2·6H2O, (2) Zn(NO3)2·6H2O and molybdenum acetate, (3) Zn(NO3)2·6H2O and molybdenum nitrate; The molar ratio of the metal elements in the two metal salts is 1:2 to 1:
20.
2. The method for preparing a bimetallic selenide heterostructure according to claim 1, characterized in that, In step S1, the volume ratio of the sodium carboxymethyl cellulose solution, NaOH solution, H2SeO3 solution, and NaBH4 solution is (1~10):1:(1~5):(0.1~0.5). The concentration of the sodium carboxymethyl cellulose solution is 0.1-2.0 g / L. The concentration of the NaOH solution is 0.01-2.0 M. The concentration of the H₂SeO₃ solution is 0.01-2.0 M. The concentration of the NaBH4 solution is 0.01-2.0 M.
3. The method for preparing a bimetallic selenide heterostructure according to claim 1, characterized in that, In step S1, the steps for synthesizing selenium nanorods are as follows: Sodium carboxymethyl cellulose was dissolved in water, and then NaOH solution and H2SeO3 solution were added under stirring. After stirring until the solution became transparent, NaBH4 solution was added dropwise. After stirring at room temperature for a period of time, a brown suspension was obtained. The solid product was collected by centrifugation, washed three times with deionized water and ethanol, and then vacuum dried to obtain selenium nanorods.
4. The method for preparing a bimetallic selenide heterostructure according to claim 1, characterized in that, In step S2, the steps for coating selenium nanorods with a bimetallic organic framework are as follows: The selenium nanorods obtained in step S1 were dispersed in methanol, a certain amount of polyvinylpyrrolidone was added, and after stirring, methanol solutions of two metal salts were added, followed by methanol solution of 2-methylimidazole. After stirring for a period of time, the bimetallic selenide precursor was collected by centrifugation, washed several times with methanol, and then vacuum dried to obtain selenium nanorods coated with a bimetallic organic framework.
5. The method for preparing a bimetallic selenide heterostructure according to claim 1, characterized in that, In step S3, the heat preservation temperature is 600-900 ℃, and the heat preservation time is 1-6 hours. The inert gas is argon; In step S3, the steps for synthesizing the bimetallic selenide heterostructure are as follows: The selenium nanorods coated with a bimetallic organic framework obtained in step S2 were heated from room temperature to high temperature at a certain heating rate under inert gas protection, and held at high temperature for a certain time. After natural cooling, a bimetallic selenide heterostructure was obtained.
6. A bimetallic selenide heterostructure, characterized in that, The bimetallic selenide heterostructure obtained by any of the preparation methods described in claims 1-5 is composed of bimetallic selenide nanoparticles and hollow carbon nanotubes, wherein the bimetallic selenide nanoparticles are attached to the hollow carbon nanotubes.
7. The bimetallic selenide heterostructure according to claim 6, characterized in that, The diameter of the bimetallic selenide nanoparticles is 5-20 nm.
8. An application of a bimetallic selenide heterostructure, characterized in that, The bimetallic selenide heterostructure obtained by any of the preparation methods described in claims 1-5 is used to prepare electrode materials for secondary batteries.
9. The application of the bimetallic selenide heterostructure according to claim 8, characterized in that, The secondary battery is a lithium-ion battery. The bimetallic selenide heterostructure serves as the negative electrode material for lithium-ion batteries.
Citation Information
Patent Citations
A method for preparing a sodium-ion battery anode material of bimetallic selenide
CN110752356B
Preparation method of bi-metal selenide supercapacitor electrode material CuxMoySez
CN106783202A
Preparation method of bi-metal selenide sodium-ion battery cathode material
CN110752356A
